Nekatere značilnosti dvojine v slovenščini - Derganc, Aleksandra (Slavistična revija, 2006)
The article deals with dual forms in Slovenian and their use in standard Slovenian, the dialects of Slovenian and the colloquial language in Ljubljana. The article draws attention to the fact that a stronger degree of formal markedness of part of dual forms (consistent with a stronger degree of semantic double markedness of dual forms), which is a result of the the historical development, and the pragmatic value of the dual when the referenceis to two people, contribute to the vitality of this grammatical category.
Keywords: development; number (linguistics); pragmatics; pragmatika; razvoj; Slovene; Slovenian language; slovenščina; število (jezikoslovje)